PPD Pasir Puteh / Nur Nadia Azmi - Azmi, Nur Nadia (Universiti Teknologi MARA, Perlis, 2024)
At Pasir Puteh District Education Office, I have been start my journey as an intern student for six month started 4th September 2023 untill 8th February 2024. I choose this organization to do an internship training for six months to finishing my degree. I has been placed under Human Resource, ICT and Administration unit followed by the course that I already taken as an HR student. This organization is an education organization that manage all the management for school under the district. In this organization, there are four main sector with four deputies. To make sure that I can do my task and job properly, I will always have asked some guidance from my supervisor at PPD Pasir Puteh. Madam Narni is a senior executive officer at PPD Pasir Puteh so she knows how to handle intern students. Here, I have learned about human resource management, administrative and also how to do data analysis for school. Not only that, I also can handle a registration system for year one students. Education organization is not only managing education but it is also managing the whole thing in the organization such as payroll, leave applied for staff and teachers, retirement, infrastructure, school account. To assess the company, I have used SWOT analysis to highlight the strength, weakness, opportunity and threat of PPD Pasir Puteh.